El'gygytgyn impact crater, Chukotka, Arctic Russia: Impact cratering aspects of the 2009 ICDP drilling project. (2nd July 2013) - Koeberl, Christian; Pittarello, Lidia; Reimold, Wolf Uwe; Raschke, Ulli; Brigham‐Grette, Julie; Melles, Martin; Minyuk, Pavel
Abstract: The El'gygytgyn impact structure in Chukutka, Arctic Russia, is the only impact crater currently known on Earth that was formed in mostly acid volcanic rocks (mainly of rhyolitic, with some andesitic and dacitic, compositions). In addition, because of its depth, it has provided an excellent sediment trap that records paleoclimatic information for the 3.6 Myr since its formation. For these two main reasons, because of the importance for impact and paleoclimate research, El'gygytgyn was the subject of an International Continental Scientific Drilling Program (ICDP) drilling project in 2009. During this project, which, due to its logistical and financial challenges, took almost a decade to come to fruition, a total of 642.3 m of drill core was recovered at two sites, from four holes. The obtained material included sedimentary and impactite rocks. In terms of impactites, which were recovered from 316.08 to 517.30 m depth below lake bottom (mblb), three main parts of that core segment were identified: from 316 to 390 mblb polymict lithic impact breccia, mostly suevite, with volcanic and impact melt clasts that locally contain shocked minerals, in a fine‐grained clastic matrix; from 385 to 423 mblb, a brecciated sequence of volcanic rocks including both felsic and mafic (basalt) members; and from 423 to 517 mblb, a greenish rhyodacitic ignimbrite (mostly monomict breccia). The uppermost impactite (316–328 mblb) contains lacustrine sediment mixed with impact‐affected components. Over the whole length of the impactite core, the abundance of shock features decreases rapidly from the top to the bottom of the studied core section. The distinction between original volcanic melt fragments and those that formed later as the result of the impact event posed major problems in the study of these rocks. The sequence that contains fairly unambiguous evidence of impact melt (which is not very abundant anyway, usually less than a few volume%) is only about 75 m thick. The reason for this rather thin fallback impactite sequence may be the location of the drill core on an elevated part of the central uplift. A general lack of large coherent melt bodies is evident, similar to that found at the similarly sized Bosumtwi impact crater in Ghana that, however, was formed in a target composed of a thin layer of sediment above crystalline rocks.